Contribution of Organic Matter and Clay to the Cation Exchange Capacity of the Rajasthan Canal Soils - Bhatnagar, R S; Atri, S C; Mathur, G S; Choudhary, R S (Annals of Arid Zone, 2016)
Cation exchange capacity of the Rajasthan Canal Soils has been recognised in close correlation with clay, silt and organic matter contents respectively. The contribution of clay was dominant to the C.E.C. followed by O.M. and silt contents. Multiple regression equation relating clay and O.M. content. (C.E.C.=O.751 clay + 5.69 OM) with the C E.C. of soils was found more suitable than that including silt content, and can be used precisely, for prediction of C.E C. of these soils.